Positron Emission Tomography—Computer Tomography Scan Used as a Monitoring Tool Following Cellular Therapy in Cerebral Palsy and Mental Retardation—A Case Report. (3rd February 2013) - Sharma, Alok; Sane, Hemangi; Paranjape, Amruta; Gokulchandran, Nandini; Kulkarni, Pooja; Nagrajan, Anjana; Badhe, Prerna
Abstract : Cerebral palsy (CP) is one of the non-progressive neurological diseases caused by damage to the brain tissue at birth, which leads to physical, cognitive and perceptive symptoms. Even after lifelong medical and therapeutic management there are residual deficits which affect the quality of life of the patients and their families. We examined a maximally rehabilitated, 20 year old male suffering from CP and Mental Retardation (MR). He had diplegic gait and Intelligence Quotient (IQ) score of 44 with affected fine motor activities, balance, speech and higher functions. Positron Emission Tomography—Computer Tomography (PET-CT) scan identified frontal, temporal, parietal, occipital, left cerebellar lobes, amygdala, hippocampus, and parahippocampus as the affected areas. He was treated with cellular therapy of Autologous Bone Marrow Derived Mono-Nuclear Cells (MNCs) transplantation followed by multidisciplinary rehabilitation. Six months following therapy, PET-CT scan showed significant increase in metabolic activity in all four lobes, mesial temporal structures and left cerebellar hemisphere, also supported by clinical improvement in IQ, social behavior, speech, balance and daily functioning. These findings provide preliminary evidence to support the efficacy of cellular therapy for the treatment of CP with MR. PET-CT scan can also be viewed as an impressive tool to monitor the effects of cellular therapy.